MILK COLLECTION POINTS: INOVASI KEMITRAAN USAHA TERNAK SAPI PERAH DI PANGALENGAN-BANDUNG SELATAN - Anugrah, Iwan Setiajie; Purwantini, Tri Bastuti; Erwidodo, nFN (Analisis Kebijakan Pertanian, 2021)
The fulfillment of national milk consumption is still facing the problem of low production, productivity and quality of milk from smallholder dairy farmers. Efforts to improve the performance of dairy farming are continuously being made, one of which is partnership cooperation between the milk processing industry, dairy farmers and dairy cooperative. This paper aims to analyze the success of an innovative partnership between the Frisian Flag Indonesia (FFI) milk processing industry and farmers who are members of the South Bandung Dairy Cooperative (KPBS) Pangalengan through the management of the Milk Collection Point (MCP) program. The study results indicate that the cause of the low quality of fresh milk is influenced by the number of initial bacteria in fresh milk, the milk supply chain from farmers to the milk processing industry is too long, and the cooling system is inadequate. The low quality is the cause of the low selling price of fresh milk. The MCP program has not only succeeded in improving the quality of fresh milk but has also provided price incentives for farmers. Dairy farmers who are members of the KPBS receive incentives to improve the dairy cattle management process in the MCP program's direction. It is recommended that cooperation between dairy farmers, the milk processing industry, and dairy farmer cooperatives should continue to be developed to encourage an increase in milk volume and quality as raw material for the milk processing industry. This effort is expected to have an impact on increasing the income and welfare of the dairy farmers in Indonesia.AbstrakPemenuhan kebutuhan susu nasional masih menghadapi permasalahan rendahnya capaian produksi, produktivitas dan kualitas susu dari peternak sapi perah rakyat. Berbagai upaya untuk meningkatkan kinerja peternakan sapi perah rakyat terus dilakukan, salah satunya berupa kerja sama kemitraan antara industri pengolahan susu dengan peternak dan koperasi peternak sapi perah. Tulisan ini bertujuan untuk menganalisis keberhasilan sebuah inovasi kemitraan antara industri pengolahan susu Frisian Flag Indonesia (FFI) dengan para petermak yang tergabung dalam Koperasi Persusuan Bandung Selatan (KPBS) Pangalengan melalui pengelolaan program Milk Collection Point (MCP). Hasil kajian menunjukkan bahwa penyebab rendahnya kualitas susu segar dipengaruhi oleh jumlah bakteri awal pada susu segar, rantai pasok penyetoran susu dari peternak kepada industri pengolahan susu terlalu panjang, dan sistem pendingin yang kurang memadai. Rendahnya kualitas menjadi penyebab rendahnya harga jual susu segar. Program MCP tidak saja berhasil meningkatkan kualitas susu segar juga telah memberikan insentif harga bagi peternak. Para peternak yang tergabung dalam KPBS memperoleh insentif untuk meningkatkan proses pengelolaan usaha ternak sapi perah ke arah yang dipersyaratkan oleh program MCP. Kerja sama antara peternak sapi perah, industri pengolahan susu, dan koperasi peternak dapat terus dikembangkan sehingga dapat mendorong peningkatan volume dan kualitas susu sebagai bahan baku industri pengolahan susu. Upaya ini diharapkan berdampak pada peningkatan pendapatan dan kesejahteraan peternak sapi perah di Indonesia.